'Striving for freedom or remaining with what is well-known': a focus-group study of self-management among people with type 1 diabetes who have suboptimal glycaemic control despite continuous subcutaneous insulin infusion. Issue 4 (1st April 2022) - Persson, Margareta; Leksell, Janeth; Ernersson, Åsa; Rosenqvist, Ulf; Hörnsten, Åsa
Abstract : Introduction: Continuous subcutaneous insulin infusion (CSII) treatment is beneficial for obtaining glycaemic control for many persons with type 1 diabetes mellitus (T1DM). Still, some individuals do not obtain improved HbA1C levels despite CSII treatment, and there is a lack of evidence regarding how psychosocial factors may influence glycaemic control. Thus, we aimed to explore the attitudes and experiences of self-management among people with T1DM and suboptimal glycaemic control despite CSII treatment. Research design and methods: A qualitative inductive design was applied, and four FGDs were performed with 37 adult men and women of various ages and duration of T1DM. All participants had suboptimal glycaemic control despite CSII treatment. Transcripts were analysed using qualitative manifest and latent content analysis. Results and conclusion: The themes Searching for freedom and flexibility and Preferring safety and the well-known illustrated the divergent psychosocial strategies adapted, which both resulted in suboptimal glycaemic control. The technical devices and their effects on glycaemic levels may be challenging to understand and adjust to fit people's lifestyles. The rapid advances of technology devices in diabetes care can potentially change peoples' lives, but is the educational support developing as fast? Multifaceted web-based education of high quality, including tailored support with a person-centred focus, is more important than ever before as the need for technical knowledge and understanding may put further disease burdens to patients with T1DM on CSII treatment.